Erectile dysfunction and quality of life in patients under left ventricular assist device support − an unspoken issue - Aiste Monika Jakstaite; Peter Luedike; Simon Wernhart; Markus Kamler; Arjang Ruhparwar; Tienush Rassaf; Maria Papathanasiou (International Journal of Cardiology: Heart & Vasculature, 2023)
Background: Multiple domains of quality of life (QoL) such as erectile function are not sufficiently investigated among left ventricular assist-device (LVAD) patients. We aimed to evaluate the prevalence of erectile dysfunction (ED) and its association with QoL and depression. Methods: This is a prospective, single-center, cross-sectional study. We included adult male LVAD patients who were clinically stable after at least 3 months post-implantation. Erectile function was assessed with the International Index of Erectile Function (IIEF-5) questionnaire with a score of ≤21 being confirmatory for ED. QoL and depression were estimated with the Kansas City Cardiomyopathy Questionnaire (KCCQ) and the Patient Health Questionnaire depression scale (PHQ-8), respectively. Results: The study included 56 patients, of whom 45 (80 %) met criteria for ED, a prevalence much higher than previously reported in patients with established cardiovascular disease or conservatively treated heart failure. Patients with ED were older and had lower 6-minute walking distance. ED was not associated with comorbidities and heart failure medications but with less frequent use of diuretics and phosphodiesterase-5 inhibitors. There was a correlation between erectile function and depression as well as QoL. Conclusions: These findings underscore that ED deserves special attention and should be included in a multi-targeted approach to address suboptimal QoL outcomes after LVAD implantation.